Răspuns :
[tex]a) \sqrt{63} - 3(2 \sqrt{7} - 4 \sqrt{3} ) + 4(2 \sqrt{3} + 5 \sqrt{7} )[/tex]
[tex] = 3 \sqrt{7} - 6 \sqrt{7} + 12 \sqrt{3} + 8 \sqrt{3} + 20 \sqrt{7} [/tex]
[tex] = 17 \sqrt{7} + 20 \sqrt{3} [/tex]
[tex]b) - 2( \sqrt{12} - \sqrt{2} ) + 5( \sqrt{3} - \sqrt{8} ) - 7( 3 \sqrt{3} + 9 \sqrt{2} )[/tex]
[tex] = - 2 \times 2 \sqrt{3} + 2 \sqrt{2} + 5 \sqrt{3} - 5 \times2 \sqrt{2} - 21 \sqrt{3} - 63 \sqrt{2} [/tex]
[tex] = - 4 \sqrt{3} + 2 \sqrt{2} + 5 \sqrt{3} - 10 \sqrt{2} - 21 \sqrt{3} - 63 \sqrt{2} [/tex]
[tex] = - 20 \sqrt{3} - 71 \sqrt{2} [/tex]
[tex] = 3 \sqrt{7} - 6 \sqrt{7} + 12 \sqrt{3} + 8 \sqrt{3} + 20 \sqrt{7} [/tex]
[tex] = 17 \sqrt{7} + 20 \sqrt{3} [/tex]
[tex]b) - 2( \sqrt{12} - \sqrt{2} ) + 5( \sqrt{3} - \sqrt{8} ) - 7( 3 \sqrt{3} + 9 \sqrt{2} )[/tex]
[tex] = - 2 \times 2 \sqrt{3} + 2 \sqrt{2} + 5 \sqrt{3} - 5 \times2 \sqrt{2} - 21 \sqrt{3} - 63 \sqrt{2} [/tex]
[tex] = - 4 \sqrt{3} + 2 \sqrt{2} + 5 \sqrt{3} - 10 \sqrt{2} - 21 \sqrt{3} - 63 \sqrt{2} [/tex]
[tex] = - 20 \sqrt{3} - 71 \sqrt{2} [/tex]